Lexical diary of a pandemic – descriptive contrastive dimension in the Italian-Polish context - Szpingier, Beata Katarzyna (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
Considering the fact that languages are defined by users and remains in constant evolution, the main goal of this paper is to focus on how to reflect the contemporary situation through the terms relating to the period of crisis due to the coronavirus pandemic. The descriptive contrastive dimension of the analysis (ACD) is proposed with reference to the Italian-Polish context and with regard to the different language solutions (semantic, semiotic and structural) such as: resemantization, types of loanwords (adapted and not adapted, semantic casts and structural casts), medical technicalities, vocabulary of politicians and others government institutions. Referring to some theories, implemented in today’s circumstances, such as the linguistic relativism of Benjamin Lee Whorf (1950 : 52-55) and the observations of Ludwig Wittgenstein (1953), current article current article also reflects the application of Aristotle’s considerations concretized in Rhetoric (330 BCE).